A critical analysis of the 2008 mediation in Zimbabwe: an exploration of the main debates and criticisms - Walker, Caroline (Department of Political Studies, 2014)
Since independence in 1979 Zimbabwe has experienced periods of great conflict and instability. The chief explanation for this is the ruling party ZANU-PF's monopolistic attitude to rule. The party has historically quashed attempts at opposition, drawing its political legitimacy from its role in the liberation struggle. 2008 election results favouring the opposition lead to ZANU-PF inflicted violence, including retributive attacks on former ZNAU-PF supporters. The SADC mandated an Mbeki-lead mediation following this violence. Mugabe accepted the mediation due to historically minimal criticism from Mbeki, yet had no intention to sincerely share power with opposition MDC factions. Even though ZANU-PF was in a legitimacy crisis it refused to cede power. This is clearly evident in the poor implementation of GPA and resuscitation of old problems as well as the development of new problems between the parties. The extent of the legitimacy crisis is an important issue here. Even though some critics laud the mediation as a landmark in the country's history and attribute it some success, the lack of respect for the agreement undermines these notions. The case highlights the difficulty for a mediator to bring positive peace, especially in the context of an historically one-party militarized state. It has further bearing on mediation in general when it shows how mediation success can only be judged in the long run, regarding parties' implementation of agreements. If power patterns remain the same post mediation, as they do in Zimbabwe, the mediation should be seen as a failure.